Žinioms valdyti palanki aukštųjų universitetinių mokyklų bibliotekų organizacinė elgsena - Lymantaitė, Kristina (Information & Media, 2010)
Šiandienė žmogaus, grupės, organizacijos veikla yra grįsta žiniomis, todėl vis dažniau mokslininkai kalba apie palankių sąlygų joms kurti ir jomis dalytis sudarymą organizacijose. Tačiau tiek bendrojoje, tiek bibliotekininkystės literatūroje analizuojamas tik pavienių organizacijos elementų vaidmuo kuriant žinioms valdyti palankią aplinką. O būtinas visuminis požiūris, kurį pabrėžia organizacinės elgsenos teorija, nagrinėjanti visus žmonių elgesio ir santykio su organizacijos aplinka aspektus. Remiantis šia teorija galima teigti, kad, formuojant žinioms valdyti palankią aplinką aukštųjų universitetinių mokyklų bibliotekose, svarbūs visi organizacinės elgsenos lygmenys: individo, grupės, organizacijos. Tik atskleidus visų šių lygmenų įtaką žinioms valdyti, galima identifikuoti žinioms valdyti palankios bibliotekų organizacinės elgsenos požymius, o palyginus su esama bibliotekų organizacine elgsena, teikti sprendimus didinti šios elgsenos tinkamumą žinioms kurti ir jomis dalytis. Straipsnio tikslas – apibrėžti žinioms valdyti palankios bibliotekų organizacinės elgsenos požymius, tokios elgsenos kūrimo problemas ir teikiamas galimybes. Uždaviniai: išanalizuoti individo, grupės, organizacijos elgseną bibliotekose, pabrėžiant šių lygmenų vaidmenį kuriant žinioms valdyti palankią aplinką; įvertinti žinioms valdyti tinkamos organizacinės elgsenos kūrimo problemas ir galimybes, atsižvelgiant į specifinius bibliotekų kaip organizacijų vidaus ir išorės veiksnius. Rašant straipsnį remtasi teoriniais mokslinio tyrimo metodais (analizės, apibendrinimo, lyginimo, sintezės). Pagrindiniai žodžiai: organizacinė elgsena, žinių valdymas, biblioteka. Knowledge Management-friendly Organizational Behaviour of Academic Libraries Kristina Lymantaitė Summary The low public sector efficiency, poor quality of public services shape the negative attitude toward public sector organizations. Therefore, the search of tools that would help libraries increase their efficiency, competitiveness, service quality and gain greater acceptance in society is nowadays particularly relevant. One of the possible solutions is to make library organizational behaviour, knowledge management-friendly and thus to allow the usage of the existing and encourage the creation and sharing of the new knowledge. A comprehensive analysis of library organizational behaviour elements allows to define the key features of knowledge management-friendly organizational behaviour. The definition of these features is a basis for the further research on library organizational behaviour. An analysis of the current situation of libraries organizational behavior and a comparison with the appropriate knowledge management features would allow organizing practical recommendations. The feature of knowledge management-friendly library organizational behavior that may be considered fundamental is organizational culture which is based on trust, and which fosters creativity. However, the knowledge management-friendly library organizational behaviour can only be formed at all behaviour levels (the employee, group, organization). Unfortunately, the current situation is aggravated by the fact that there is no instrument to assess the library’s organizational behaviour (in the knowledge management perspective), and there is no uniform explicit guidance to implement these changes. The creation of these tools may be considered as an area for the further research and follow-up studies. The specificity of a library as an organization, the context of changes, and the overall economic situation of the country’s instability (leading to the declining library funding) creates even more barriers for a successful organizational behaviour. Therefore, we can start with changing library’s organizational culture, because it is the most influential element, and does not require a lot of investment. Creation of knowledge management-friendly library organizational behaviour offers a possibility to implement the goals of a library and its workers and offer new competitive services for customers in order to meet their needs and expectations. A library, by disclosing the intellectual capital, becomes a flexible, innovative, entrepreneurial and learning organization and the center of learning and knowledge for both its employees and customers, and gains a leading position in the knowledge-based society.